The Jewish Study Bible: By Adele Berlin and Marc Zvi Brettler, eds. (New York: Oxford University Press, 2004. 2,143 pages.) (American Journal of Islam and Society, 2005)
Jabès’ aphorism captures the challenge to readers of scripture: how to preservethe immaculate experience of the ineffable through a finite languageof maculate perception. The Jewish Study Bible [JSB] is a testament to thehuman struggle with the divine as read through diverse interpretive lensesthroughout the ages. Editors Berlin and Brettler, along with Fishbane, havecompiled a first-rate Hebrew Bible that fuses the technically adept JPSEnglish translation along with introductions, annotations, and essays bymany of today’s established and burgeoning scholars. This model is basedupon The New Oxford Annotated Bible (p. xi), which abridges in-depthessays by contemporary scholars into accessible versions for general readersand undergraduate students. The balance between North American and ...